ALIH PENGETAHUAN DAN POLA HIDUP MASYARAKAT KECAMATAN SEKOTONG TERKAIT STUNTING MENGGUNAKAN METODE FRES & P SERTA INSTRUMEN BOOKLET BESTI PADU - Puspitasari, Candra Eka; Lestarini, Ima Arum; Ekawanti, Ardiana; Nofrida, Rini; Ardinia, Gusti Ayu Eka Radha; Alhidayah, Nachwa Humaira; Bakhraeni, Bakhraeni; Tsania, Siti Hamida Rahayu; Erlangga, Ithnan Baqi Putra; Ananta, Abdurahman (Universitas Mataram, 2024)
Stunting is a condition where a child experiences a lack of nutritional intake which causes growth disorders such as height below the standard of children of the same age in a toddler. Stunting can be caused by multifactors, including food consumption that is less nutritious. Sekotong sub-district is one of the marine product producing areas in West Nusa Tenggara, however the prevalence of stunting among children aged 6 months to 2 years in this area is still above the stunting threshold set by the Ministry of Health of the Republic of Indonesia. Therefore, it is necessary to shifting knowledge and lifestyle to targeted communities to reduce the risk of stunting in Sekotong District with the aim of educating the community and creating new good habit patterns. This activity was carried out using the FRES&P method (Family, Refreshing, Education, Sociality, and Presentation) to 42 people involved in the community including health cadres in the Sekotong Health Centre working area. The activity was carried out by providing exposure to material where an assessment of understanding was carried out before and after the exposure was carried out. In between activities, games related to the material were given to make it easier for participants to understand the material. In addition, the distribution and explanation of the material in the BESTI PADU booklet was carried out by applying ‘Matur Tampiasih’ to all participants present. This booklet is expected to be one of the learning tools for participants during the activity and when returning to their homes. The activity went smoothly and received good enthusiasm as evidenced by the various questions given by the participants. In addition, based on the results of the analysis of questionnaires distributed to participants, it was found that there were changes in the level of understanding resulting from the activity. The FRESH&P method can be one of the socialisation methods regarding stunting. Therefore, it can be concluded that the educational method provided can increase public understanding of stunting.